Assessing Disease Severity in COVID-19 Patients: Correlations with Laboratory, Radiological, Comorbidity, and Blood Gas Parameters - Ghazala Jawwad; Mehvish Iftikhar; Anjum, Aiman Farogh; Maleha Asim (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the lab investigations, blood gases analysis, and radiological findings to assess the severity of COVID disease in positive patients with comorbidities. Study Design: Cross-Sectional Study. Place and Duration of Study: Railway Hospital, Rawalpindi, and Services Hospital, Lahore, Pakistan, from Dec 21 to Apr 22. Methodology: Data of 750 patients, admitted in Railway Hospital Rawalpindi and Services Hospital Lahore, were gathered, and WHO categories of COVID-19 disease severity were used, and correlated with TLC, HbA1c, CRP, LDH, pH, and oxygen requirement at baseline. Results: Significant differences were observed among mild, moderate, severe, and very severe categories of COVID-19 patients concerning Total Leukocyte Count (TLC)(p=0.001), Hemoglobin A1c (HbA1c) (p=0.006), C -reactive protein (CRP) (p=0.001), Lactate Dehydrogenase (LDH) (p=0.010), oxygen saturation (SpO2) (p=0.001), pH(p=0.001), and oxygen requirement at baseline(p=0.034). Additionally, there was significant correlation between disease severity and HbA1c(r=0.244, p=0.003), TLC(r=0.458, p< 0.001), ferritin(r=0.260, p=0.001), C-reactive protein(r=0.443,p<0.001), LDH(r=0.211,p=0.01), and pH(r=0.653, p<0.001) and oxygen requirement at baseline(r=0.669, p<0.001). Significant associations with co-morbidities were seen in relation to severe and very severe COVID-19 disease (p-value ≤0.001) Conclusion: Patients with severe and very severe disease were found to have raised levels of TLC, HbA1c, CRP, LDH, pH, and oxygen requirement at baseline; additionally, there is a strong association of comorbidities with severe and very severe disease.